The Role of Negative Politeness in Request: The Strategies that Non-Native Speakers Apply and Fail to Apply when Performing Request - Marazita, Licenciada Romina Ariana (Journal of NELTA, 2010)
As native speakers of a particular language, we are aware of its use as one of the most powerful tools for communication. The way we use language not only conveys a social aspect- that we are part of a speech community and share a discourse accent- but also shows the way we are: our personality, our ambitions, our power, our solidarity, etc. All these aspects, among many others, come into play in a conversation. The aim of this article is to analyze if non-native speakers are aware of the concept of negative politeness and how many different strategies they apply or fail to apply when performing requests. The strategies to be observed will be useful to identify the possible absence of pragmatic ability and the feasible teaching implications to improve pragmatic competence in non-native speakers; and, at the same time, reflect upon new approaches for the teaching of English as a foreign language. Key words: Pragmatic competence, speech acts, politeness, negative politeness, face DOI: 10.3126/nelta.v14i1.3094 Journal of NELTA Vol.14, No 1&2, 2009 December Page: 82-90